Valence and Ambivalence: Science and Poetry in the Philippine Anglophone Tradition - Garcia, J. Neil C. (Philippine Humanities Review, 2015)
In the first two sections of this paper, the author surveys the troubled history of science and modernist poetry, and identifies the operations of metaphor and analogical thinking as the foremost contract zone between these two “realms.” He then discusses, in the third section, the salience of this insight in relation to the question of Philippine poetry in English, which he argues to be, by definition, representationally complex and ironic. This leads him to the idea that modernist-inspired “avant-garde” experimentations have generally not “prospered” in the Philippines’s anglophone poetic tradition precisely because their “condition for possibility” (a scientificized cultural ground) cannot be said to have fully taken root in this neocolonially indentured country in the Global South. On the other hand, a critical awareness of this tradition’s linguistic and cultural complexity should reveal that “self-reflexive” moments (typically exclusively associated with modernist aesthetics) are, after all, already very much in evidence in it. The paper ends with a presentation of science-themed poems by a selection of outstanding Filipino poets. Keywords: Poetry, Science, Philippine Literature, Modernism, Representation